Para que não se esqueça : a memória da ditadura brasileira (1964-1985) nos livros didáticos de história do ensino médio - Piccoli, Camila Maria (My University, 2018)
The study presents approaches on Human Rights in the teaching of History, to understand the importance of reflection on the Brazilian Civil Military Regime texts present in the main textbooks distributed by the National Program of High School Didactic Book, for the maintenance of Human Rights? In this way, the objective of this work is to analyze how the Brazilian Military Dictatorship is approached in the textbooks of the History of the Secondary School, taking especially into consideration the question of Human Rights. The approach will be based on discourse analysis, according to Orlandi, and content analysis, according to Bardin. In addition, possibilities will be suggested for approaching the theme in the classroom. The final product proposal is the production of a website on the subject, which can be accessed by teachers and students from public and private educational networks, the general public interested in the subject, undergraduate and graduate students, as well as other researchers from the area. The reflections point out that the violation of human rights occurred institutionally by the Brazilian State and is still present in the public and private spaces of society, therefore, permanent analysis in the teaching of history tends to contribute to diminish such action.
O estudo apresenta abordagens sobre Direitos Humanos no ensino de História, a fim de compreender qual a importância da reflexão sobre o Regime Civil Militar Brasileiro nos textos presentes nos principais livros didáticos distribuídos pelo Programa Nacional do Livro Didático para o Ensino Médio, para a manutenção dos Direitos Humanos? Desta forma, o objetivo deste trabalho é analisar como a Ditadura Civil Militar Brasileira é abordada nos livros didáticos de História do Ensino Médio, tendo presente, especificamente, a questão dos Direitos Humanos. A abordagem terá como base a análise de discurso, segundo Orlandi, e a análise de conteúdo, segundo Bardin. Além disto, serão sugeridas possibilidades para a abordagem do tema em sala de aula. A proposta de produto final é a produção de um site sobre a temática, o qual, posteriormente, poderá ser acessado pelos professores e estudantes das redes pública e privada de ensino, público geral interessado pela temática, estudantes de graduação e pós-graduação, assim como outros pesquisadores da área. As reflexões apontam que a violação aos Direitos Humanos ocorreu de forma institucionalizada pelo estado brasileiro e que se faz presente ainda em espaços públicos e privados da sociedade, portanto, a análise permanente no ensino de história tende a contribuir para diminuir tal ação.
Keywords: Ditadura - Brasil; Direitos humanos; História - Estudo e ensino; História (Ensino médio); Livros didáticos; Brasil - História; Brasil - Política e governo - 1964-1985; Dictatorship - Brazil; Human rights; History - Study and teaching; History (High school); Textbooks; Brazil - History; Brazil - Politics and government - 1964-1985